The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.33619/2414-2948/63/01
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Pollution Strategy of Artemisia and Chenopodiaceae

Abstract: It is known that 30–40% of people in the world population are sensitized to pollen. This phenomenon is exacerbated in contaminated and urbanized areas. Wormwood is one of the main herbaceous allergenic plants, and its pollen is among the ten global aeroallergens. An allergy to it is a common phenomenon on a global scale. The role of pollen the etiology of pollinosis is usually in tandem with wormwood pollen established in Russia, Central Asia and Kazakhstan, Europe and America. The purpose of this article was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previously, allergic rhinitis from ragweed pollen was successfully addressed using a commercial product, Pollinex Quattro (Allergy Therapeutics, UK), which contains plant pollen extracts treated with glutaraldehyde, absorbed on L-tyrosine, and adjuvanted with monophosphoryl lipid A (MPL) injected four times 1 week apart ( 23 ), resulting in remission of symptoms for the duration of the allergy season ( 20 ). Wormwood pollen is among the top 10 global aeroallergens that cause allergic rhinitis and bronchial asthma ( 24 ). The goal of this pilot study, therefore, was to similarly test an ultrashort adjuvanted ASIT regimen for wormwood pollen-induced allergic bronchial asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, allergic rhinitis from ragweed pollen was successfully addressed using a commercial product, Pollinex Quattro (Allergy Therapeutics, UK), which contains plant pollen extracts treated with glutaraldehyde, absorbed on L-tyrosine, and adjuvanted with monophosphoryl lipid A (MPL) injected four times 1 week apart ( 23 ), resulting in remission of symptoms for the duration of the allergy season ( 20 ). Wormwood pollen is among the top 10 global aeroallergens that cause allergic rhinitis and bronchial asthma ( 24 ). The goal of this pilot study, therefore, was to similarly test an ultrashort adjuvanted ASIT regimen for wormwood pollen-induced allergic bronchial asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies in mice ( 11 ) showed that it is possible to achieve effective therapy of bronchial asthma caused by wormwood pollen ( Artemisia ), one of the ten global aeroallergens ( 12 ), with only four injections (at weekly intervals) of a vaccine based on the recombinant Art v 1 Artemisia vulgaris major protein formulated with ISA-51 adjuvant. However, it is not known whether this vaccine formulation in an ultrashort ASIT regimen can be effective in the treatment of allergic rhinitis, the presence of which has been recognized as an important risk factor for bronchial asthma ( 13 ).…”
Section: Introductionmentioning
confidence: 99%